2017
DOI: 10.33425/2639-9474.1011
|View full text |Cite
|
Sign up to set email alerts
|

Traditional Reproductive Health Practices among Women in South-South Nigeria

Abstract: Despite the development of orthodox health services in Nigeria, several traditional reproductive health practices for women still thrive in many indigenous populations. These practices relate to delayed menarche, delay in child bearing/infertility, during pregnancy and lactation. Mixed method design (descriptive and focused ethnographic) was utilized to explore and elicit traditional reproductive health practices for women of childbearing age, and perceptions about their use. Two hundred and fifty seven (257) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 4 publications
1
0
0
Order By: Relevance
“…This agrees with a study from a developing country where birth asphyxia was reported as a significant cause of CP [16]. It could be that these women may have patronized unskilled personnels like traditional birth attendants and maternity homes due to their traditional believes, a practice that is predominant among women in developing countries [17]. The preponderance of Spastic CP cases in our study and spastic quadriplegia as the commonest subtype is similar to that reported by two previous studies [16,18].…”
Section: Discussionsupporting
confidence: 90%
“…This agrees with a study from a developing country where birth asphyxia was reported as a significant cause of CP [16]. It could be that these women may have patronized unskilled personnels like traditional birth attendants and maternity homes due to their traditional believes, a practice that is predominant among women in developing countries [17]. The preponderance of Spastic CP cases in our study and spastic quadriplegia as the commonest subtype is similar to that reported by two previous studies [16,18].…”
Section: Discussionsupporting
confidence: 90%